Acute Ochratoxin A exposure induces inflammation and apoptosis in human embryonic kidney (HEK293) cells. (October 2017) - Raghubeer, Shanel; Nagiah, Savania; Chuturgoon, Anil A.
Abstract: Ochratoxin A (OTA), a common contaminant of grain and fruit and known carcinogen, has been linked to impaired antioxidant response and cellular repair. The effect of OTA on inflammation in cells has not been explored. This study investigated OTA's influence on inflammatory mediators using a range of OTA concentrations (0.5 μM (sub-IC50 ), 1.2 μm (IC50 ) and 2 μm (supra-IC50 )) on human embryonic kidney (HEK293) cells over 24hr. The markers of inflammation in HEK293 cells were evaluated using the following techniques: western blotting (phosphorylated (p-)NFκB (Ser536), p-IKK (Ser176/180) and p-p53 (Ser392), total NFκB, IKK, IκBα and p53), luminometry (caspases 1, 3/7, 8, 9, ATP) and ELISA to determine IL-1β levels. The results indicate increased activation of the inflammatory pathway in the sub-IC50 concentration, evidenced by significant increases in p-NFκB ( p = 0.0006). The IC50 concentration indicates decreased inflammatory induction supported by decreased levels of IL-1β and caspase 1 ( p = 0.0186 and p = 0.0068 respectively) with decreased IKK and increased IκBα ( p = 0.0046 and p = 0.0006 respectively). Furthermore, a decrease in inflammatory pathway activation was seen in O3 (increased IκBα, p < 0.05) coupled with increased apoptosis via elevated caspase 3/7 ( p = 0.0002), 8 ( p = 0.0011) and 9 activity ( p = 0.0002); as well as decreased ATP levels. This data suggests a new mechanism of OTA toxicity and its involvement in inflammation, kidney disease and fibrosis. Highlights: Ochratoxin A (OTA), a known renal toxicant, induces oxidative stress and DNA damage. The sub-IC50 (0.5 μM) concentration of OTA activates the canonical NFκB pathway during acute exposure in HEK293 cells. OTA induces inflammation and apoptosis by increasing phosphorylated NFκB (Ser536) and activating caspases 8, 9 and 3/7. The IC50 (1.2 μM) concentration of OTA decreases IL-1β and caspase 1 levels, decreasing the inflammatory response. OTA stimulates the p53-mediated DNA repair process by upregulating protein levels of phosphorylated p53 (Ser392).